Soft ruthenium and hard Brønsted acid combined catalyst for efficient cleavage of allyloxy bonds. Application to protecting group chemistry. Issue 37 (16th September 2015) - Tanaka, Shinji; Suzuki, Yusuke; Saburi, Hajime; Kitamura, Masato
Abstract: We show that a monocationic CpRu(II) complex of quinaldic acid (QAH) and a monocationic CpRu(IV)(π-allyl)QA complex catalyze efficient cleavage of the allyloxy bond in allyl ethers, allyl esters, allyl carbonates, and allyl carbamates in methanol without the need for additional nucleophiles. The only co-product is volatile allyl methyl ether, enhancing operational simplicity during isolation of the deprotected alcohols, acids, and amines. This clean and high-performance catalytic system should contribute to protecting group chemistry during the multistep synthesis of pharmaceutically important natural products. Full details of this system, including the mechanism, are reported. Graphical abstract: